Suhu, Kelembaban dan Kebisingan pada Halaman Rumah Toko di Jalan Godean, Sleman, Yogyakarta - Vita Dini Anggraeni; Sri Muryani; Rizki Amalia (Poltekkes Kemenkes Yogyakarta, 2016)
The reduction of open land in urban areas affects air circulation. Shop-houses which stand in rows along the sreets without providing space for plants can affect environmental health. An observation carried out on 4th May 2015 at one of shop-houses in Godean Street km 6,5 Sleman, obtained results of temperature, humidity and noise measurement as much as 40,2 °C, 35,7 % and 86,2 dB(A), which was meant that those three parameters has exceeding the corresponding thresholds. Vertical garden is one of planting techniques which do not need large area. The objective of the research was to know the influence of vertical garden to the change of temperature, humidity and noise on the front yard of shop-houses in Godean Street, by conductinngan experimthent with post-test only control group design. The types of plants used were yellow palm, yellow bamboo and lidah mertua. The data were analyzed by using independent t-test at ? = 0,05. From ten shop-houses sample, the results show that temperature decreased in an average of 0,6 °C (1,97 %), humidity increased in an average of 0,25 % (0,57 %), and noise decreased in average of 0,959 dB (A) (1,297 %). For temperature and humidity, there was no significant difference was found between the treatment and control groups (the p-values were0,153 and 0,918, respectively). Meanwhile for noise, the significant difference was identified (pvalue = 0,048). Based on the findings, the shop-houses owners are recommended to apply vertical garden as green hedge and as one of the efforts to reduce the noise.